Surface mass balance in 2005–2012 derived using shallow radar stratigraphy over Blåskimen Island, Western Dronning Maud Land - Goel, Vikram; Matsuoka, Kenichi (Norwegian Polar Institute, 2017)
This dataset provides SMB estimates for Blåskimen Island ice rise, western Dronning Maud Land. It was estimated using englacial reflectors visible in radar stratigraphy, dated using 23-m deep firn core, It provides an average annual SMB for past 9 years from 2014 along the radar profiles. In this estimate, the same density-depth profile obtained using a 23 m deep firn core near the summit is used along all the profiles. For more on the method refer to Goel et al., (2017). The data are provided in MATLAB (.mat) file format named ‘IRD_smb_radar.mat’ consisting struct-class variables for each radar profile as ‘Profile_1’, Profile_2’ etc. Profile_1 includes – • ‘x’ and ‘y’ arrays with coordinates in a polar stereographic projection parallel to 71° S (EPSG 3031), and ‘z’ shows elevations above the WGS84 ellipsoid. All are in the unit of meters. • ‘smb_const’ array with the second SMB estimate using constant density-depth profile in kg m-2 • ‘dis’ array with distance from the starting point in meters. See the following manuscript for further details: Goel, V., Brown, J., and Matsuoka, K.: Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica, The Cryosphere Discuss., https://doi.org/10.5194/tc-2017-61, in review, 2017.